Strategi Penggunaan TikTok Sebagai Microlearning Untuk Mengoptimalkan Pemahaman Materi Pembelajaran Mahasiswa - Halimatus Sa'diah; Atika Muliyandari (Berkah Smart Academica, 2025)
This study aims to formulate a strategy for using TikTok as microlearning to optimize students' understanding of learning information. The research method used a literature review by examining accredited journals, books, and scientific documents related to TikTok, microlearning, and digital usage strategies. The literature criteria included reputable journals that discussed social media-based learning or microlearning and were relevant to the focus of the study. The results of the study indicate that TikTok has great potential as a microlearning medium due to its short (15-60 seconds), concise, and easy-to-understand video format. Effective strategies include: (1) presenting content with a focus on one core concept per video, using supporting visuals and text, and a clear delivery structure, (2) student engagement strategies through the platform's interactive features, (3) strategies to reinforce understanding of information through repetition and content variation, and (4) solutions to overcome the challenges of using TikTok. This research fills a gap in the literature by presenting a structured TikTok-based microlearning strategy focused on improving students' academic information comprehension in the digital age.